STATUS DAN STRATEGI PENGELOLAAN LINGKUNGAN PERHOTELAN DI KAWASAN KOTA MADYA DILI TIMOR - LESTE - Alvares, Adalgisa D.D.G.; Suyasa, Budiarsa; Paturusi, Syamsul A. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2017)
STATUS AND STRATEGY OF HOSPITALITY ENVIRONMENTAL MANAGEMENT IN DILI TOWN TIMOR - LESTE The research held about to reach two goals. To find out the condition and the strategy about the management of hotel environment at Dili. The decision of area research is held with purposive. All hotel in Dili will be chosen as the samples, it means that it will be held with census. Next, as the respondents in this research is the manager of the hotels. The result of this research shows that there are seven variables. They are the loyalty for its regulation, the programme and appreciation of environment, green park and space, the management of waste water, the management of rubbish, the management of emission, the management of non enviromental things. The indicator of the regulation (rules) of the company can be identified by using AMDAL document. The indicator of the programme and appreciation of environment can be identified by using the policy and appreciation that is dotained from this  environment. The indicator of waste water management, can be recognized by using IPAL. The indicator of rubbish management can be recognized by using its mechanism. The indicator of emission management can be recognized by using its mechanism. The indicator of non environmental things management can be identified by using its mechanism. The level of this implementation for the hotel environment at Dili is about 65,08 % (Fairly). The implementation of per variable can be seen that the percentage of the loyalty for its regulation is about 74,8 % (good), the programme and appreciation of environment is about 44 % (not good), green park and space is about 76,8 % (good), the management of waste water is about 81,6 % (good), the management of rubbish is about 60,8 % (fairly), the management of emission is about 63,2 % (fairly), the non enviromental things management is about 54,4 % (fairly). The indicator supported by the environment needs the attention of hotel management which improves the hotel image for tourist or guests in the hotel.